PERAN SELF-COMPASSION TERHADAP LONELINESS PADA DEWASA AWAL PASCA PUTUS CINTA DALAM HUBUNGAN BERPACARAN - Hana Fajariyah; Evanytha (MANASA, 2025)
Loneliness may arise after an individual experiences a breakup, characterized by feelings of sadness, melancholy, loss of motivation, and low self-esteem. One factor that can reduce loneliness is self-compassion, namely, a kind and understanding attitude toward oneself when facing suffering. This study aims to examine the role of self-compassion in loneliness among early adults after a breakup in a romantic relationship. The research employed a quantitative approach involving 210 participants aged 20–40 years who had experienced a breakup within the past two weeks to five months, selected using purposive sampling. The instruments used were the Self-Compassion Scale (Neff, 2003) and the UCLA Loneliness Scale Version 3 (Russell, 1996). Validity and reliability were assessed using the Rasch model, which showed that the scales had good validity and reliability. The data were collected through an online questionnaire and analyzed using simple linear regression. The results indicated that self-compassion had a significant and negative role in loneliness. It means higher self-compassion contributed to lower loneliness. This study recommends developing psychological interventions on self-compassion to reduce the emotional impact of a breakup.